Reforming the Custody System: Loss of Custody and Relinquishment of Custody as Examples - Youssef Lachgar (International Journal of Scientific Research and Innovative Studies, 2025)
This study examines the legal and judicial framework governing the loss and relinquishment of child custody under Moroccan family law. It highlights the legislative philosophy underlying custody as a mechanism to protect the best interests of the child while ensuring parental responsibility. Based on a detailed analysis of judicial decisions of the Moroccan Court of Cassation, the paper identifies the main causes of custody termination, including circumvention of visitation rights, remarriage of the custodial mother to a foreigner, and voluntary or implicit relinquishment. It also analyses inconsistencies and ambiguities within Articles 173–176 of the Family Code and evaluates their practical application in light of Maliki jurisprudence. The research concludes that the current framework requires reform to ensure gender equality, protect the psychological well-being of the child, and prevent misuse of custody and visitation provisions. Recommendations include legal recognition of joint custody, clarification of waiver conditions, and stronger judicial oversight to safeguard the child’s best interests. Keywords: Child custody; Moroccan Family Code; Court of Cassation; Judicial interpretation; Custodial rights; Relinquishment of custody; Visitation rights; Parental equality; Best interests of the child; Family law reform. Received Date: August 21, 2025 Accepted Date: September 13, 2025 Published Date: October 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/441